ANALYSIS METHODS FOR DETERMINING THE CURRENT CLIMATE FOR TRANSMISSION LINE LOADING - , О. Д., В. Ф. (Municipal economy of cities. Series: «Economy science», 2013)
The influence of environmental stress on the elements of lines and analyzed the effectiveness of modern methods of control and prevention of their effects.